Cystic Necrosis of the Spinal Cord in Compressive Cervical Myelopathy: Demonstration by lopamidol CT-Myelography - Jinkins, John R.; Bashir, Rifaat; Al-Mefty, Ossama; Al-Kawi, M. Zuheir; Fox, John L. (American Journal of Neuroradiology, 1986)
Seven consecutive patients with compressive cervical myelopathy were studied with standard water-soluble contrast myelography and immediate CT followed by delayed CT of the spinal canal at 10 to 12 hr. Every case demonstrated findings suggestive of necrosis and/or cavitation of the central portions of the spinal cord on the delayed CT study. Two types of abnormalities were visualized in the form of delayed collections of contrast media inside the cord: (1) bilateral enhancement, a double-barreled “snake-eyes” appearance at or near the level of compression (consistent with central gray matter necrosis and/or cavitation—local syringomyelia ex-vacuo); and (2) longitudinally oriented, “pencil-shaped” central enhancement of variable length distant from the level of compression (consistent either with an enlarged central canal—hydromyelia exvacuo—or with necrosis and/or cavitation extending craniad and caudad from the area of maximal compression and located in or near the anterior portion of the dorsal columns—distant syringomyelia ex-vacuo). These findings, supported by previous reports of autopsy specimens, may explain in part: (1) the frequent discrepancy between the levels of maximal cervical compression and the variable neurologic signs; and (2) the frequent lack of improvement in clinical signs after surgical decompression of the spinal cord at this late stage of the illness. We believe similar intramedullary lesions may be present in other cases of chronic compression of varying etiology at any location within the spinal cord.